2023
DOI: 10.1038/s41467-023-35828-2
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the catalytic mechanism of superoxide dismutase activity of carbon dot nanozyme

Abstract: Nanozymes with superoxide dismutase (SOD)-like activity have attracted increasing interest due to their ability to scavenge superoxide anion, the origin of most reactive oxygen species in vivo. However, SOD nanozymes reported thus far have yet to approach the activity of natural enzymes. Here, we report a carbon dot (C-dot) SOD nanozyme with a catalytic activity of over 10,000 U/mg, comparable to that of natural enzymes. Through selected chemical modifications and theoretical calculations, we show that the SOD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
97
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 206 publications
(125 citation statements)
references
References 67 publications
4
97
0
Order By: Relevance
“…[ 40 ] They concluded that the carboxyl groups on the surface of GQDs were the substrate‐binding sites, the carbonyl groups were the catalytically active sites, and the hydroxyl groups inhibited the catalytic activity. In our latest work, [ 42 ] we reported a C‐dot nanozyme with ultra‐high SOD‐like activity (>10000 U mg −1 ). The catalytic mechanism was revealed by surface modifications and theoretical calculations: The carboxyl and hydroxyl groups on the surface of C‐dots capture superoxide anions through hydrogen bonds, while the carbonyl groups coupling with the π‐system take part in electron transfer processes during disproportionation of superoxide anions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 40 ] They concluded that the carboxyl groups on the surface of GQDs were the substrate‐binding sites, the carbonyl groups were the catalytically active sites, and the hydroxyl groups inhibited the catalytic activity. In our latest work, [ 42 ] we reported a C‐dot nanozyme with ultra‐high SOD‐like activity (>10000 U mg −1 ). The catalytic mechanism was revealed by surface modifications and theoretical calculations: The carboxyl and hydroxyl groups on the surface of C‐dots capture superoxide anions through hydrogen bonds, while the carbonyl groups coupling with the π‐system take part in electron transfer processes during disproportionation of superoxide anions.…”
Section: Resultsmentioning
confidence: 99%
“…[ 47 ] Here, by utilizing functional group protection strategies, we reveal that all of the carboxyl, hydroxyl and amino groups on the surface of C‐dots are closely related to the SOD enzymatic activity, which was consistent with our latest work. [ 42 ] Considering the N‐doped graphitic crystal structure and conjugated framework of C‐dots, we proposed a possible catalytic mechanism. The superoxide is anchored to the surface of the C‐dots through the hydrogen bond with the carboxyl group, hydroxyl, and amine groups.…”
Section: Resultsmentioning
confidence: 99%
“…Carbon-based nanomaterials have gained popularity in biomedicine because of their desirable physical and chemical characteristics, biocompatibility, and ability to mimic various enzymes. Such materials have great mechanical qualities and can be used as wound dressings; examples are fullerene, graphene and its derivatives, carbon nitride, carbon dots (CDs), and carbon nanotubes (CNTs) . The peroxidase-like activity of a series of oxidized carbon nanotubes (o-CNTs) produced by Wang et al was exceptional throughout a broad pH range.…”
Section: Nanozymesmentioning
confidence: 99%
“…Such materials have great mechanical qualities and can be used as wound dressings; examples are fullerene, graphene and its derivatives, carbon nitride, carbon dots (CDs), and carbon nanotubes (CNTs). 64 The peroxidase-like activity of a series of oxidized carbon nanotubes (o-CNTs) produced by Wang et al 65 was exceptional throughout a broad pH range. The carbonyl-group on the oxidized carbon nanotube surface served as an active catalytic core, with the hydroxyl and carboxyl groups serving as competing sites.…”
Section: Nanozymesmentioning
confidence: 99%
“…Over the past two decades, nanomaterials with enzyme-like characteristics, termed nanozyme, have attracted great attention because of their easy preparation, good stability in harsh conditions, and low cost. Up to now, a variety of nanomaterials have been discovered with enzyme-mimicking activity, such as transition metal oxide-based nanomaterials [ 14 , 15 , 16 , 17 ], noble metal- or metal-based nanostructures [ 18 , 19 , 20 ], carbon-based nanomaterials [ 21 , 22 , 23 ], and metal–organic framework-based nanostructures (MOFs) [ 24 , 25 , 26 ]. Although some progress has been made in this field, conventional nanozymes still face great challenges such as insufficient enzyme-like activity and low selectivity compared with natural enzymes.…”
Section: Introductionmentioning
confidence: 99%